Ureteroscopy Is Equally Efficient and Safe in Obese and Morbidly Obese Patients: A Systematic Review and Meta-Analysis - Wang, Wei; Gao, XiaoShuai; Peng, Liao; Jin, Tao (Frontiers in Surgery, 2022)
Background Ureteroscopy (URS) has been established as an effective treatment for stones in obese patients. However, recent studies found that efficacy of the procedure may be lower in patients with higher BMI. In the current study, we aim to determine if obesity might influence the effectiveness and safety of URS. Methods In May 2021, a comprehensive search was conducted in the PubMed, EMBASE, Web of Science, Cochrane Library, ClinicalTrials.gov to find eligible studies. Stone-free rate (SFR), operative time, length of stay, and complication rate were assessed utilizing RevMan 5.3. Results Thirteen studies involving 4583 normal-weight patients (NWP), 2465 obese patients (OP), and 291 morbidly obese patients (MOP) were included. Pooled results showed that statistically similar SFR existed between OP and NWP (OR: 1.09; 95% CI: 0.79, 1.52; p = 0.59), and between MOP and NWP (OR: 1.03; 95% CI: 0.46, 2.31; p = 0.95). The operation time was similar between OP and NWP (MD: -2.27; 95% CI: -8.98, 4.43; p=0.51), and between MOP and NWP (MD: 4.85; 95% CI: -5.78, 15.47; p=0.37). In addition, no significant difference regarding length of stay existed between OP and NWP (MD: -0.07; 95% CI: -0.20, 0.07; p=0.33), and between MOP and NWP (MD: -0.06; 95% CI: -0.25, 0.14; p=0.58). Furthermore, we observed similar minor complication rate between OP and NWP (OR: 1.04; 95% CI: 0.81, 1.32; p = 0.78), and between MOP and NWP (OR: 1.29; 95% CI: 0.80, 2.08; p = 0.30). The differences concerning major complication rate between OP and NWP (OR: 0.97; 95% CI: 0.39, 2.43; p = 0.95), and between MOP and NWP (OR: 2.01; 95% CI: 0.55, 7.30; p = 0.29) were also not significant. Conclusions Our study demonstrated that URS performed in MOP and OP appear to have the same efficacy and safety as well as in NWP group.